Rapid Development of Multimodal Interactive Systems: A Demonstration of Platform for Situated Intelligence - Bohus, Dan; Andrist, Sean; Jalobeanu, Mihai (ICMI 2017 Proceedings of the 19th ACM International Conference on Multimodal Interaction, 2017)
We demonstrate an open, extensible platform for developing and studying multimodal, integrative-AI systems. The platform provides a time-aware, stream-based programming model for parallel coordinated computation, a set of tools for data visualization, processing, and learning, and an ecosystem of pluggable AI components. The demonstration will showcase three applications built on this platform and highlight how the platform can significantly accelerate development and research in multimodal interactive systems.